Evaluasi Status Kesuburan Tanah di DAS Yeh Ho Kabupaten Tabanan Berbasis Sistem Informasi Geografis Untuk Menentukan Arahan Pengelolaan Lahan - SIPAYUNG, JHON YANSEN; ARTHAGAMA, I DEWA MADE; SUPADMA, A.A. NYOMAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2020)
Evaluation of Soil Fertility Status at the Yeh Ho watershed of Tabanan Regency Based on Geographic Information Systems to Determine Land Management This study aims to determine the status of soil fertility in the Yeh Ho waterahed, Tabanan Regency and to determine the limiting factors for soil fertility in the Yeh Ho Watershed, Tabanan Regency. Provide fertilization directions based on the results of evaluation of soil fertility status in the Yeh Ho Watershed, Tabanan Regency and provide information in the form of a map of soil fertility status based on a geographic information system. The method used in taking soil samples in the study area is the field survey method by first making homogeneous land units obtained through overlaying several thematic maps such as soil type maps, slope class maps and land use maps then each land unit is sampled purposively. sample which is then composited. Soil samples that have been obtained are then analyzed in the laboratory for soil chemical properties including, Cation Exchange Capacity (CEC), Base Saturation (BS), C-Organic Soil, P-Total, K-Total, pH. The results of the analysis of soil chemical parameters are then evaluated on the status of soil fertility based on PPT (1995).The results showed that in the Yeh Ho watershed in Tabanan Regency there were three classes of soil fertility status namely high fertility class (T) consisting of 2 namely land units IV and VII (Jatiluwih Village and Rejasa Village), and medium fertility class (S) consisting of 10 namely land units II, III, V, VI, VIII, IX, X, XI, XII and XIII (Jatiluwih Village, Penatahan Village, Wangaya Gede Village, Tangguntiti Village, Senganan Village and Dalang Village), while those with low fertility classes include 1 land unit, namely I (Desa Beraban). Two soil fertility parameters which are limiting factors are the low P-total and K-total values. Alternative management measures to overcome these two limiting factors are the addition of phosphorus fertilizer, potassium fertilizer and organic matter.